TOWARDS SUSTAINABLE COMMUNITY AND INSTITUTIONAL RESPONSE TO CLIMATE EXTREMES: A SITUATIONAL ANALYSIS OF INSTITUTIONS, COMMUNITIES AND THEIR RESPONSE TO CLIMATE CHANGE INDUCED DISASTERS IN UTTARAKHAND - Malathi Adusumalli; Kavita Arora (European Scientific Journal, ESJ, 2015)
This paper presents a situational analysis of disaster in 2013 and issues related to the preparation of mountain communities in Uttarakhand with specific reference to Bhatwari Block in Uttarkashi District and their adaptation and response. It also anlayses the response of the institutions in the light of needs of the communities. The paper argues that the determinants for such a response are located in the information flow and access, resource access and governance. The need for looking at these responses in the light of Mountain vulnerability frameworks and sensitivity aspects which include both gender and social marginality issues are emphasized. The issues of gendered vulnerability of the mountain communities located in a fragile eco system and inequitious social system with specific reference to agricultural and forest based livelihoods are discussed. The paper also focuses on how these vulnerabilities are impacted by climate change. The paper argues that institutional contexts also influence the responses of adaptation and mitigation. The paper concludes with suggesting some mechanisms for preparation of the communities and institutions for a sustainable response.